Human-animal relationship during surgical clinical procedure and postoperative calf Holstein Black and White stricken by anal atresia: Case Report - Amaral, Jackson Barros do; Trevisan, Guilherme (Pubvet, 2018)
This relate tells the objective of describing human-animal relation during clinical-surgical treatment and postoperative treatment in Holstein calf treated by anal atresia and its possible effects on well-being and gaining weight. Anal atresia is a congenital malformation with occlusions in the challenge and anus that occurs in animals and in human. The well-being of animals afflicted by pain and suffering in the postoperative can be influenced by the human-animal relationship. The animal was born in 2016 and after 48 hours, it was found atresia anal grau II, suggestive of pain and suffering. Emergency surgery was performed such as sedation, local anesthesia and epidural. The evaluation of the welfare was performed by clinical, behavioral, and physiological and weight gain hair. In the postoperative antibiotic, anti-inflammatory and polyvitamins were administered. After surgery, elimination of gases and mechanics was observed, following normal evacuations until discharge. The surgical wound showed good conditions; however, the feces presented blood strains, fibrin and rectal tense. The animal normalized the appetite and appeared active and how vigorous at the end of the surgery, explored the environment and used the soft bed at moments of rest and vocalize before breastfeeding. Chopped hay and ration were available, which favored an alteration in the consistency of the feces, going from semipastosa to pasture. In the postoperative, human-animal interaction was established, where it was possible to observe positive accounts such as dropping out, dropping fingers, scratching humans, demonstrating playful behaviors such as persecutions, acrobatics, jump-in, running, manipulations as targets, air and head. The physiological indicators were normalized. The weight gain was 11 kg in 25 days. It is concluded that during the first 30 days, the surgical and operative clinical treatment the animal presented a good clinical evolution and that humanitarian care as "positive" actions in the human-animal relationship influenced the welfare and gain of weight.
Keywords: anorectal anomaly; welfare; bovine; surgery; congenital malformation